Allergic contact dermatitis from ("hypoallergenic") adhesives containing D‐limonene. (5th December 2021) - Dendooven, Ella; Foubert, Kenn; Naessens, Tania; Pieters, Luc; Lambert, Julien; Goossens, An; Aerts, Olivier
Abstract: Background: Besides being a potential component of (some species of) colophonium, D‐limonene is also used as a tackifier in the production of adhesives. Hydroperoxides of limonene are well‐known skin sensitizers. Objectives: To show that D‐limonene may be present in colophonium‐containing but also colophonium‐free ("hypoallergenic") adhesives, and that patients suffering from allergic contact dermatitis (ACD) from both types of adhesives might display positive patch test reactions to limonene hydroperoxides in this regard. Methods: Five patients with suspected ACD from adhesives were patch tested to the baseline series (containing limonene hydroperoxides 0.3 and 0.2% pet.), additional series and, if available, to the culprit adhesives. The adhesives labelled as containing colophonium (n = 3) or free from it (n = 2) were analysed with gas chromatography ‐ mass spectrometry (GC‐MS) for the presence of D‐limonene. Results: All five patients sensitised to adhesives had (strong) positive patch test reactions to limonene hydroperoxides. The presence of D‐limonene, and/or related components, could be demonstrated in all three colophonium‐containing and, surprisingly, also in two colophonium‐free ("hypoallergenic") tapes. Conclusions: D‐limonene may be present in both regular and "hypoallergenic" adhesives, with limonene hydroperoxides potentially contributing to ACD from such medical devices. The use of fragrance chemicals in adhesives deserves further research. Abstract : D‐limonene is a component of colophonium and is also used on its own as a tackifier in adhesives. Its oxidation products, including hydroperoxides, are well‐known skin sensitisers. Patients with allergic contact dermatitis from colophonium‐containing and "colophonium‐free" adhesives may therefore show relevant positive patch test reactions to limonene hydroperoxides. The use of fragrance chemicals in adhesives and the potential link between fragrance and adhesive contact allergy deserves further research.